Analisis Consumer Behaviour Pada Toko Retail Dengan Metode APRIORI-SD - Nathaniel Edward; Rolly Intan; Alvin Nathaniel Tjondrowiguno (Jurnal Infra, 2019)
Retail store needs to evolve especially in digital age where ecommercebecoming more and more common and most peopleprefer the convenience of an e-commerce. One of the biggestadvantage of a “newer” e-commerce is they build they’rebusiness model on the foundation of processing data, whereasolder retail store doesn’t. Development of data mining andmachine learning are pushing older business model to do better.This journal represents the possibilities of using subgroupdiscovery as a method of analyzing transactional data. Subgroupdiscovery is a data mining technique which extracts interestingrule. APRIORI-SD is a method within subgroup discovery whereevaluation measure use by APRIORI-SD already prioritizingunusualness distribution of a given data.The result of this knowledge are able to find anomalies such asdifferentiating subgroup(s) with differences up to 50% comparedto overall distribution percentage. With the result people areable to create a better strategies in the future.